Controllable preparation of an ice cream-shaped hollow sphere array. Issue 15 (22nd March 2022) - Liu, Yang; Sun, Xinlong; Zhao, Feng; Zhan, Fei; Zhang, Bo; Fu, Jun-Heng; Wang, Lei; Liu, Jing
Abstract : In a hydrothermal environment, EGaIn liquid droplets in hole arrays transfer from liquid state into solid hollow spheres. They hold much air between the solid and liquid interface, enhancing the thermal insulation and superhydrophobic performance. Abstract : Hollow microspheres with high specific surface area are widely used in thermal insulation, drug delivery and sustained release, catalysis and optical absorption. Eutectic gallium–indium (EGaIn) undergoes phase transformation and oxidation when heated in aqueous solution, which can provide a crystal seed and preferential growth environment for nanomaterials. Therefore, it is very promising to further study the application of liquid metal in functional and structural nanomaterials. In this study, a EGaIn-based ice cream-shaped hollow sphere array with nanostructures was firstly synthesized on the designed hole array model using a hydrothermal process, and then the surface was further modified by fluorination to form a superhydrophobic film. Different sizes of the hollow Eutectic gallium–indium zinc oxide (EGaIn-ZnO) microspheres could be easily achieved by varying the size of the model, hence leading to controllable wettability. Furthermore, hollow microspheres hold much air, making it feasible for application in the field of anti-ice and thermal insulation.